Undang-undang harta intelek di Malaysia - Khadijah Mohamed; Ahmad Shamsul Abd. Aziz.; Universiti Utara Malaysia (Sintok : Penerbit Universiti Utara Malaysia, 2006)
Understanding the concept of intellectual property law in Malaysia
Rujukan : p. 177-180.
Keywords: Intellectual property -- Law and legislation -- Malaysia